Valor preditivo da cintigrafia de perfusão miocárdica ou da ressonância magnética cardíaca na avaliação da doença arterial coronária obstrutiva num cenário da vida real - Silva, Cláudia (2023)
Introduction and objectives: Randomized controlled trials comparing stress cardiac magnetic resonance (CMR) and single-photon emission computed tomography (SPECT) suggest similar diagnostic accuracy for detecting obstructive coronary artery disease (CAD). There are few data on whether this remains true in routine clinical practice. The aim of this study was to assess clinical and angiographic characteristics of patients undergoing invasive coronary angiography (ICA) after stress CMR or SPECT, and to compare their positive predictive value with published results from the CE-MARC trial. Methods: In this retrospective tertiary-center analysis, we included 429 patients undergoing ICA after a positive stress CMR or positive SPECT performed within the previous 12 months. Obstructive CAD was defined as any coronary artery stenosis ≥50% in a vessel compatible with the ischemic territory on stress testing. Results: Of the total 429 patients, 356 (83%) were referred after a positive SPECT, and 73 (17%) after a positive stress CMR. Patients did not differ according to age, cardiovascular risk factors, previous revascularization or left ventricular dysfunction, but patients with SPECT were more frequently male (p=0.046). The prevalence of obstructive CAD was similar in patients with positive SPECT vs. positive stress CMR (76.1% vs. 80.8%, respectively, p=0.385). The positive predictive values of both techniques were similar to those reported in the CE-MARC trial. Conclusion: In this tertiary center analysis, stress CMR and SPECT showed similar positive predictive values, comparable to those reported in the CE-MARC trial. This finding supports the emerging adoption of CMR in clinical practice for the diagnosis and management of CAD.